Study of some biochemical parameters in penitent with type II diabetes mellitus - W. Qader, Alaa; K. Al-Hashemi, Wisam (Al-Nahrain Journal of Science, 2022)
Type 2 diabetes (T2DM) is a growing global health concern that usually occurs in adults which accounts for about 90% of the population. The diabetic in type II diabetes mellitus begins with insulin resistance [1]. This form of diabetes typically exists in citizens over the age of forty, however, it is now being diagnosed more frequently in young adults and children who are overweight [2]. This study involved 130 subjects, divided into 30 subjects as control and 100 subjects as diabetics group. For each analysis were done:  blood sugar, HbA1c, blood urea, blood creatinine, lipids profile (T.Cholesetrol, triglyceride, LDL, HDL, and VLDL), and CRP. The findings revealed significantly higher (p≤0.01) along with all parameters concentration of diabetes in comparison with the control group.